Development of the creative sector in Kazakhstan (Journal of Economic Research & Business Administration, 2021)
In this era of extraordinary change and globalization, many recognize that the creative industries aredriving the new economy. Industries of the creative sector of the economy are increasingly recognizedas significant for both social and economic development and are attracting growing interest of the worldcommunity. The understanding and study of the economic value of creative industries has expanded.It was clear that they have an impact on GDP growth and employment and can improve the foreigntrade position and competitiveness of the country, as well as contribute to revitalizing and promotingthe brand of creative cities and attracting investment. Many authors recognize that creative industrieshave a significant impact on the development of the economy and society, thanks to the implementationof a new concept of economic growth and development, and that they represent one of the feweconomic sectors in which dynamic development is expected in the future. This review presents theresearch results of a study of the development of creative industries in one of the Post-Soviet countries– Kazakhstan. The research methodology, including the analysis of interviews, reveals several barriers tothe development of the creative sector of the economy. This study helps us understand how the creativeeconomy is developing in a transition country.Key words: creative industries, creative economy, barriers, Kazakhstan.